Risk factors for nodal failure after radiochemotherapy and image guided brachytherapy in locally advanced cervical cancer: An EMBRACE analysis. (October 2021) - Peters, Max; de Leeuw, Astrid A.C.; Nomden, Christel N.; Tanderup, Kari; Kirchheiner, Kathrin; Lindegaard, Jacob C.; Kirisits, Christian; Haie-Meder, Christine; Sturdza, Alina; Fokdal, Lars; Mahantshetty, Umesh; Hoskin, Peter; et al.
Highlights: Nodal disease, tumour width and local failure are risk factors for NF post-treatment for LACC. Any CI nodes without PAO nodes' and 'any PAO nodes' are stronger risk factors than 'small pelvis' nodes. Elective PAO-irradiation was associated with significantly less NFPAO . Abstract: Objective: To assess risk factors for nodal failure (NF) after definitive (chemo)radiotherapy and image-guided brachytherapy for locally advanced cervical cancer (LACC) for patients treated in the EMBRACE I study. Materials and methods: Data for pelvic NF and para-aortic (PAO) NF (NFPAO ) were analysed. After multiple imputation, univariable and multivariable Cox-regression was performed for clinical and treatment-related variables. For patients with affected pelvic nodes but no PAO nodes at diagnosis, additional analyses were performed for two subgroups: 1. 'small pelvis' nodes in internal and external iliac, obturator, parametrial, presacral and/or common iliac (CI) region and 2. any CI nodes (subgroup of 1). Results: 1338 patients with 152 NF and 104 NFPAO events were analysed with a median follow-up of 34.2 months (IQR 16.4–52.7). For the entire group, larger tumour width, nodal risk groups (in particular any CI nodes without PAO nodes), local failure, and lower Hb-nadir increased the risk of NF. Elective PAO-irradiation was independently associated with a decreased risk of NFPAO (HR 0.53, 95%-CI 0.28–1.00, p = 0.05). For subgroup 1, having 'any CI nodes without PAO nodes' and local failure significantly increased NF risk. Additionally, elective PAO-irradiation was associated with less risk of NFPAO (HR 0.38, 95%-CI 0.17–0.86, p = 0.02). For subgroup 2 only local failure was associated with higher risk of NF. Conclusion: In this patient cohort, nodal disease and tumour width at diagnosis, as well as local failure, are risk factors for NF after definitive treatment. Having either 'any PAO nodes' (with or without pelvic nodes) or 'any CI nodes' (without PAO nodes) are stronger risk factors than involvement of nodes in the small pelvis alone. Elective PAO-irradiation was associated with significantly less NFPAO, particularly in patients with nodal disease in the 'small pelvis' and/or CI region at time of diagnosis.